THE BASIS OF CRITERIA FOR EVALUATING TRANSLATION (Journal of Foreign Language Studies, 2020)
Until now, researchers have not agreed on the criteria for evaluating the quality of a translation. Some propose to replace the criteria “tín (fidelity), đat (normative), nhã (best writing style)” often mentioned in literary translation by other clearer criteria. Others recommend applying models of foreign authors in the evaluation of translation. In short, there is no research on the theoretical and practical basis for developing evaluation criteria. This article justifies a new approach which highlights the need to develop evaluation criteria on the basis of examining translation competence. This approach helps to establish a set of precise and scientifically based criteria.
Keywords: evaluation criteria; translation competence; quality of translation